(3QSGdI JJYdb HGdSf GdKGdK Edi BNQ GdYeQs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s
(3ChdgG (B:s
(3aCLed eG CfTCg GdeTGjN , hChdi eG bUO GONGQI ef GdCfJaGY , Yde jYe faYg s
(3BNQgG (B:s
(3aEf hGab JYdjbg HGdbHhd aef aVdg hEdGadjSHd Pjd GdeSGeMI Ydi eG jQGg ef GdPdd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B92 s
(3eUOQ GbJfGA GdCUd (B:s
(3ShgGL (B(41(6)) s
Keywords: (3GdWHs